Unreal, unsheltered, unseen, unrecorded: The multiple invisibilities of LGBTQI+ homeless youth. (August 2021) - Norris, Michelle; Quilty, Aideen
There is significant research evidence which demonstrates that LGBTQI+ young people experience higher rates of homelessness than their straight and cis peers. However, estimates of the scale of their over representation in homelessness vary significantly. This partially reflects difficulties in identifying and researching LGBTQI+ homeless youth due to their invisibility within homeless services. Drawing on in-depth interviews with homeless LGBTQI+ youth in Dublin and other Irish cities and with policy makers, homeless service providers and advocacy group representatives, this article reflects on the causes and implications of this invisibility. As its title suggests, the article identifies four interrelated causes of the invisibility – the unreal, unsheltered, unseen and unrecorded nature of LGBTQI+ youth homelessness. The article examines how these factors individually and collectively perpetuate the invisibility of LGBTQI+ homeless youth, impede their access to services for homeless people and reduce the likelihood that homeless services will be tailored to meet their needs and enable them to successfully exit homelessness.